1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Equation of a sphere in XYZ coordinates

  1. Sep 9, 2016 #1
    1. The problem statement, all variables and given/known data
    Show that the equation represents a sphere, and find its center and radius.

    3x2+3y2+3z2 = 10+ 6y+12z

    2. Relevant equations

    3. The attempt at a solution
    3x2+3y2-6y +3z2 -12z =10

    My equation is how the constants in-front of the squared terms affect the sphere formula? Besides that I should be completing the square for the Y and Z terms right?
  2. jcsd
  3. Sep 9, 2016 #2


    Staff: Mentor

    What is the formula for the equation of a sphere? That would have been good to put in the Relevant equations section.
  4. Sep 9, 2016 #3
    The formula of a sphere is
    R2=(X-X0)2 +(Y-Y0)2 +(Z-Z0)2

    So I tried working further and eventually got to
    (Y-1)2 =13/3

    3Z2-12Z =13/3
    3X2 +(Y-1)2+(Z-6)2= 37.44
    so R2=37.44 and R=6.12
  5. Sep 9, 2016 #4

    Ray Vickson

    User Avatar
    Science Advisor
    Homework Helper

    Your "equations" ##3Y^2-6y=10##, ##(Y-1)^2 = 13/3##, etc., are meaningless in this problem. You are trying to find constants ##a, b, r## so that the equation
    $$3 x^2+3 y^2 + 3 z^2 -6y - 12z - 10 = 0$$
    $$3 x^2 + 3 (y-a)^2 + 3 (z-b)^2 - r^2 = 0$$
    The second equation must hold for ALL values of ##x,y,z## that satisfy the first equation, and vice-versa.
  6. Sep 11, 2016 #5


    User Avatar
    Staff Emeritus
    Science Advisor
    Homework Helper
    Education Advisor

    You shouldn't drag the constant term from the original equation along. Instead, you can say
    3y^2 - 6y &= 3(y^2-2y)\\
    &= 3[(y^2-2y+1)-1]\\
    &= 3(y-1)^2 - 3.
    \end{align*} Note that ##3y^2-6y=3(y-1)^2-3## holds for all y whereas the equation you started with, ##3y^2-6y=10##, doesn't. (Also, don't use y and Y interchangeably. It's sloppy and incorrect.)

    The original equation can then be rewritten as
    3x^2 + (3y^2 - 6y) + (3z^2-12z) &= 10 \\
    3x^2 + [3(y-1)^2 - 3] + (3z^2-12z) &= 10 \\
    3x^2 + 3(y-1)^2 + (3z^2-12z) &= 13

    You should check your work in completing the square. I don't get (z-6)^2.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted